Analisis Generic Strategy Model Michael Porter Pada PT. Cahaya Murni Borneo Timur Untuk Menentukan Pilihan Strategi Di Balikpapan - H, Syahril; Bachtiar, Bachtiar (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2016)
The manufacture industry is one of the industries that produce springbad, furniture and its elements. The number of competitors with their product differentiation as well as the government policy to be the cause of this rivalry. PT. Cahaya Murni Borneo Timur is one of the companies that compete in this industry, so companies should create a strategy to win the competition in the market. The method used is a qualitative research method with data collection techniques with a purposive sample. This study aimed to analyze the competitive environment and the industry's best options strategies on PT. Cahaya Murni Borneo Timur using Generic Strategy from Michael E. Porter.Keywords: Competitive Strategy, industry competition environment, the choice of the best strategy, Generic Strategy Analysis.